Efeito anticonvulsivante do monoterpeno sintético (1S)-(-)-verbenona em animais de laboratório por metodologias específicas comportamentais - Melo, Cynthia Germoglio Farias de (2017)
Verbenone is a natural organic compound classified as a terpene, being naturally found in a variety of plants. The (1S) - (-) - verbenone (VRB) is a naturally occurring pheromone generated by beetles from a host tree resin precursor, α-pinene. Essential oils containing (1S) - (-) - verbenone have antibacterial, acaricidal and anti-inflammatory activity. However, no anticonvulsant activity was studied with this terpene. Thus, this work aims to evaluate the potential anticonvulsant effect of VRB through specific behavioral methodologies, performed through chemical and electrical induction of convulsion in mice, as well as quantify proinflammatory cytokines, gene expression and histopathological analysis of the animals treated in the chronical model (kindling). VRB did not cause any alteration in the motor coordination of the animals. VRB showed no effect on the pilocarpine-induced convulsion test and strychnine, suggesting that VRB may not act on cholinergic neurotransmission as well as glycine receptors. In the electroshock-induced seizure test, only the dose of 250 mg / kg; i.p. showed effect, however, was not able to inhibit the presence of seizures. In the PTZ-induced seizure test, VRB showed anticonvulsive activity at doses of 200 mg / kg i.p. (733 ± 109.4 s) and 250 mg / kg i.p. (648.8 ± 124.5 s) significantly increasing the latency for the onset of the first seizure compared to the vehicle group (51.8 ± 2.84 s). Pretreatment with flumazenil (FLU) did not reverse the anticonvulsant effect of VRB. VRB showed no reduction in IL-1β, IL-6 and TNFα cytokines, but was able to increase BDNF and COX-2 gene expression and reduce c-fos levels. VRB did not present an anticonvulsive effect in the chronic model, but its treatment showed a reduction in the death of the neural cells in the hippocampus of the mice. The findings suggest that the anticonvulsive effects of VRB in the PTZ test may be related to modulation of COX-2, BDNF and c-fos messenger RNA expression.